1985
DOI: 10.1007/bf03010047
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylactoid reactions to vancomycin during anaesthesia: two clinical reports

Abstract: Vancomycin is becoming increasingly used for pro

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

1986
1986
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…One serious reaction requiring respirator treatment for 2 days was observed in our study, and a similar case has been reported previously. 26 We believe that a slow vancomycin infusion under close surveillance is safe.…”
Section: '4'6'1~mentioning
confidence: 95%
“…One serious reaction requiring respirator treatment for 2 days was observed in our study, and a similar case has been reported previously. 26 We believe that a slow vancomycin infusion under close surveillance is safe.…”
Section: '4'6'1~mentioning
confidence: 95%
“…Pretreatment of patients with an antihistamine such as diphenhydramine or hydroxyzine prior to the first dose of vancomycin protects against RMS (16,17). Less common anaphylactoid reactions to vancomycin include oliguria, generalized edema, and non-cardiogenic pulmonary edema (18).…”
Section: Overview Of Vancomycin Pharmacologymentioning
confidence: 99%
“…In the case reported by Fisher 25 hypotension was due to hypovolemia. Symons et al 26 reported two cases of anaphylactoid reactions to vancomycin with an increase in systemic and pulmonary capillary pemleability. In the report by Silvemran et al 27 of an anaphylactic reaction to penicillin, there was a decrease in arterial pressure, cardiac output, and capillary pulmonary wedge pressure, and an increase in peak airway pressure, pulmonary vascular resistance and systemic vascular resistance.…”
Section: Time Rainmentioning
confidence: 99%
“…32 In man, respiratory disturbances seen during anaphylactoid and/or anaphylactic reactions are primarily bronehospasm, and less frequently pulmonary oedema. [25][26][27][28] In the monkey, Revenas et al ~3 showed that during antigen-induced anaphylaxis dynamic compliance was decreased as a result of constriction of small airways and pulmonary congestion. In the present study, the injection of cremophor EL resulted in a significant and persistent decrease in dynamic thoracopulmonary compliance.…”
Section: Time Rainmentioning
confidence: 99%